Economic Consequences of SFAS No. 33-An Insider-Trading Perspective - Ramasamy Odaiyappa; S. M. Khalid Nainar (The Accounting Review, 1992)
[The results of prior research on Statement of Financial Accounting Standards No. 33 (FASB 1979) and the effects of required disclosure of inflation have been mixed. Many studies report little or no information content for such disclosures (Beaver and Landsman 1983), although more recent studies (Bublitz et al. 1985; Lobo and Song 1989) report evidence of stock price reactions to releases of information on current cost. These studies were conducted at the aggregate level of the market and did not examine the trading behavior of particular classes of market agents. In contrast, this study focuses on the trading behavior of corporate insiders, and, instead of the commonly used security returns, a non-price variable is the dependent variable of interest. Managers (insiders) could have information about how disclosure might affect the value of a firm through political and contracting costs borne by the firm (Smith and Warner 1979; Holthausen 1981) well in advance of other traders (Jaffe 1974; Larcker et al. 1983). In conformance with their fixation on reported income and their general skepticism of market efficiency (Mayer-Sommer 1979), managers might perceive that investors would react negatively to the new information required by SFAS No. 33, especially when current-cost adjusted income falls below historical-cost income. As a consequence, they would be expected to sell their stocks in anticipation of a negative stock market reaction. For a sample of 441 firms, this study investigates the relation between the initial release of inflation-adjusted information and the trading behavior of insiders. Specifically, it is hypothesized that the expectation that disclosure income will be lower than historical-cost income leads to net selling by managers prior to the initial disclosures under SFAS No. 33. The results are generally consistent with the hypothesis. The analyses show results that are statistically significant (at conventional levels) for both the independent variables in this study-a proxy for income shrinkage and a proxy for earnings change in the expected direction. But one must keep in mind the limitations of inferences from analyses of insider-trading data (Larcker et al. 1983). Specifically, since there is no comprehensive theory of insider trading, it is difficult to interpret insidertrading activity, and the results of this study must be kept in perspective as additional evidence on the effect of SFAS No. 33 disclosures.]